2014
DOI: 10.1128/aac.03065-14
|View full text |Cite
|
Sign up to set email alerts
|

SAGA/ADA Complex Subunit Ada2 Is Required for Cap1- but Not Mrr1-Mediated Upregulation of the Candida albicans Multidrug Efflux Pump MDR1

Abstract: cOverexpression of the multidrug efflux pump MDR1 is one mechanism by which the pathogenic yeast Candida albicans develops resistance to the antifungal drug fluconazole. The constitutive upregulation of MDR1 in fluconazole-resistant, clinical C. albicans isolates is caused by gain-of-function mutations in the zinc cluster transcription factor Mrr1. It has been suggested that Mrr1 activates MDR1 transcription by recruiting Ada2, a subunit of the SAGA/ADA coactivator complex. However, MDR1 expression is also reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…For example, the SAGA/Ada complex has been shown to be important for upregulation of MDR1 expression in C. albicans (13). The SAGA complex and nuclear acetyl-CoA synthetase 2 are required for histone acetylation in yeast (37). We have shown that AR-12 blocks histone acetylation in C. albicans (10).…”
Section: Resultsmentioning
confidence: 75%
“…For example, the SAGA/Ada complex has been shown to be important for upregulation of MDR1 expression in C. albicans (13). The SAGA complex and nuclear acetyl-CoA synthetase 2 are required for histone acetylation in yeast (37). We have shown that AR-12 blocks histone acetylation in C. albicans (10).…”
Section: Resultsmentioning
confidence: 75%
“…The impact of the Swi/Snf complex on fluconazole resistance in MRR1 GOF strains is among the most severe observed among the coactivators studied to date for C. albicans zinc cluster transcription factor GOF azole resistance mutants (23,48). The deletion of snf2 reduced the fluconazole MIC in the MRR1 GOF strains to levels comparable to those of azole-sensitive MRR1 WT strains.…”
Section: Discussionmentioning
confidence: 99%
“…Nantel's group also found that Ada2-depleted C. albicans cannot express some Cap1-regulated genes under the oxidative stress condition, and that Ada2's recruitment to the promoter of Cap1-regulated genes is Cap1-dependent [19]. The way by which Ada2 regulates gene expression in a Cap1-dependent manner is consistent with the regulatory mechanism of the drug-resistant genes by Ada2 and Cap1 in C. albicans [19,42]. Although the mechanisms of how Ada2 regulates the oxidative stress-responsive genes remain to be elucidated in C. albicans, the HAT module of the SAGA complex containing Ada2 regulates some Cap1regulated genes by interacting with Cap1 transcription factor and by acetylating these genes' promoters in C. albicans ( Fig.…”
Section: Hat Module Of the Saga Complex: Its Positive Regulation Of Omentioning
confidence: 72%